Synthesizing, Studying Molecular Docking, Characterizing, and Preliminary Evaluating Anti-Bacterial Effects of Derivatives of Serotonin Contain Imidazolidine Ring - Marwa Abdullah Saleh; Karima Fadhil Ali; Basma M. Abd Razik (Al-Mustansiriyah Journal of Pharmaceutical Sciences, 2022)
This study included synthesis of new serotonin derivatives in which imidazolidine rings are present in their structures. The final imidazolidine derivatives compounds were synthesized by reaction of synthesized